Transformação de coordenadas com modelagem de distorções entre SAD69 e SIRGAS2000 com o uso de Thin-Plate Splines - Magna Junior, Joao Paulo; Camargo, Paulo de Oliveira [UNESP]; Galo, Mauricio [UNESP] (Univ Federal Parana, Centro Politecnico, 2014)
Several countries have been passed by change processes in their fundamental geodesic structure with the focus on the adoption of geocentric reference systems. In Brazil, the adoption of the SIRGAS2000 evolves the coexistence of two realizations from the COrrego Alegre system, two realizations from the SAD69 system and one realization from the SIRGAS2000 system. To make use of products in the old reference systems, methods of coordinate transformation between the existent reference frames are necessary. So, in this paper one solution for the transformation between coordinates from different reference frames, based on Thin-Plate Splines (TPS), that allows the estimation of parameters from one linear transformation and also one non-linear model is presented. The TPS model was developed to work with tridimensional coordinates and in this paper the results and analysis are performed with simulated data and also with data from the official Brazilian Geodetic System (SGB). In the check points from SAD69 stations (realization of 1996 - SAD69/96), the values of RMSE obtained were of 78,2 mm in latitude and 67,5 mm in longitude, before the transformation to the SIRGAS2000. In the comparison between the TPS model and ProGriD (Brazilian software provided by IBGE), the statistical indicators were reduced in 97%, by using the TPS model. Based in the obtained results from real dataset, the TPS model appears to be promising, since it allows improving the quality of transformation process with simultaneous distortion modeling.
Coordinate transformation with distortion modeling between SAD69 and SIRGAS2000 by using Thin-Plate Splines
Keywords: Thin-Plate Splines; Distortion Modeling; Coordinate Transformation; Reference Systems